Nutrient Utilization and Rumen Fermentation in Jalauni Sheep Fed Sorghum or Sugarcane Fodder Silage Based Diets - Awasthi, Nidhi; Das, M. M.; Singh, Sultan; Maity, S. B.; Singh, K. K.; Mishra, A. K.; Sexena, R. (Indian Journal of Animal Nutrition, 2017)
Twelve Jalauni male sheep (Av. body weight 34.6 kg, around 2-2.4 yr) were randomly assigned into two groups of six animals each. Animals in group G1 were fed sorghum silage ad lib. whereas the animals in group G2 were fed fodder sugarcane silage ad lib. Both the groups were provided 400 g of concentrate mixture daily.After adaptation period of 30 days, a 6 day metabolism trial was conducted. Before starting the metabolism trial, the rumen liquor samples were collected before feeding from each animal for two consecutive days through stomach tube. The chemical and biochemical characteristics like CP (6.44 and 6.17%), NDF (72.36 and 75.73%), pH (3.85 and. 4.15) and lactic acid (3.78 and 3.56%) contents were comparable between sorghum and foddersugarcane silage. DM intake (kg/100 kg BW or g/kg W0.75) was also similar between the groups. Digestibility coefficients (%) of DM, CP and NDF were similar in groups G1 and G2, however, OM digestibility was higher (P